2000
DOI: 10.1080/10295925.2000.9631279
|View full text |Cite
|
Sign up to set email alerts
|

Methods of improving the survival ofPinus patulaplanted into harvesting residues

Abstract: SYNOPSISThe aim of this trial was to investigate ways of improving the survival of Pinus patula seedlings when planted into areas characterised by high levels of harvesting residues (slash). The trial consisted of three non-randomised planting date treatments which spanned the 1997 -1998 summer planting season. On each of these dates, trees were planted into slash lines or areas where little or no slash had been left after harvesting. Sub-plot treatments tested whether the application of insecticide, fungicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(7 reference statements)
2
5
0
Order By: Relevance
“…The contrast of the water treatment with the control indicated that a single application of water at planting did not affect mean survival in any of the two sets of trials. This corresponded with earlier findings by Atkinson and Govender (1997), , Allan and Higgs (2000) and Rolando and Allan (2004).…”
Section: Survival At One Year After Plantingsupporting
confidence: 93%
See 3 more Smart Citations
“…The contrast of the water treatment with the control indicated that a single application of water at planting did not affect mean survival in any of the two sets of trials. This corresponded with earlier findings by Atkinson and Govender (1997), , Allan and Higgs (2000) and Rolando and Allan (2004).…”
Section: Survival At One Year After Plantingsupporting
confidence: 93%
“…In this study the application of pesticides generally improved survival significantly, as was found in other earlier trials (Atkinson and Govender, 1997;Allan and Higgs, 2000;Rolando and Allan, 2004;Rolando and Little, 2004). The application of fungicide improved survival by 12.8% on average over the control (10% significance level) and a combination of fungicide and insecticide improved survival by 29% on average over the control (5% significance level) at 365 dap.…”
Section: Survival At One Year After Plantingsupporting
confidence: 66%
See 2 more Smart Citations
“…Although there is no doubt that much of the poor survival is related to contamination/infection by F. circinatum in South Africa, it is notable that other factors also play a contributing role in survival, especially with regards to P. patula. The effects of high temperatures, drought, insects and other pathogens have all been known to affect the survival of P. patula (Morris 1990, 1991, Allan and Higgs 2000, Rolando and Allan 2004). An increase in herbicide damage to young P. patula plantings has also been noted (RGM unpublished data).…”
Section: Economic Impactmentioning
confidence: 99%